The Effects of MMP3 (rs679620) and VDR (rs731236) Gene Polymorphisms on Dental Caries: A Pilot Study. - POLAT, TOLGA (My University, 2024)
Objective Caries formation is a process affected by various factors. Studies have shown that genetic factors also play a role in caries formation. The aim of our study is to examine the effects of matrix metalloproteinase (MMP)3 (rs679620) and vitamin D receptor (VDR) (rs731236) gene polymorphisms on caries formation. Materials and Methods Following routine oral examinations in individuals aged between 20 and 44 years, the diagnosis was made according to the decayed, missing, and filled teeth(DMFT) index, and experimental groupwas definedas “highcaries risk”(DMFT 14, n¼28), and the control group as “no caries” (DMFT¼0, n¼28). Plaque index and bleeding on probing were measured from participants with a detailed anamnesis. Periodontally healthy individuals with less than 10% bleeding on probing were included in the study (n¼56). After DNA isolation fromblood samples taken fromthe participants, the genotyping of MMP3 (rs679620) and VDR (rs731236) gene polymorphisms were determined using the real-time polymerase chain reaction technique. Statistical Analysis Data were analyzed with IBM SPSS V23.0. Data distribution was evaluated with Kolmogorov–Smirnov’s test. Pearson’s chi-square test was used to compare categorical data according to groups. The results were evaluated using a significance level of p<0.05. Results Regarding MMP3 and VDR gene polymorphisms, there was a statistically significant difference between the groups in terms of MMP3 (rs679620) (p<0.001). There was no statistically significant difference between the VDR (rs731236) genotype distributions of the groups (p¼0.659). Conclusion Within the limits of this study, MMP3 rs679620 gene polymorphism may have an effect on caries formation.
Keywords: dental caries; gene polymorphism; MMP3; VDR